Palmitic acid-induced cell death: impact of endoplasmic reticulum and oxidative stress, mitigated by L-citrulline - Md. Rezwanul Habib; Yukako Tokutake; Shinichi Yonekura (Animal Bioscience)
Objective Palmitic acid (PA), the most abundant saturated free fatty acids, induces apoptosis in bovine mammary epithelial cells (MECs). It is suggested that oxidative stress and endoplasmic reticulum (ER) stress are key mechanisms underlying PA-induced cell death. This study aimed to investigate the interaction between ER stress and oxidative stress during PA-induced cell death in mammary alveolar cell-T (MAC-T) cells. Additionally, we examined whether L-citrulline can protect against PA-induced damage of MAC-T cells. Methods MAC-T cells were treated with 4-phenyl butyric acid (4-PBA) or N-acetyl-L-cysteine (NAC) to inhibit PA-induced ER stress and oxidative stress, respectively. MAC-T cells were pretreated with or without L-citrulline for 48 h followed by PA treatment. Cell viability was measured with MTT assays. Intracellular reactive oxygen species (ROS) levels in MAC-T cells were assessed using 5-(and-6)-chloromethyl- 2′,7′-dichlorodihydrofluorescein diacetate acetyl ester dye. Real-time quantitative polymerase chain reaction was used to explore the regulation of genes associated with oxidative stress, and ER stress genes. Western blotting analysis was also carried out. Results 4-PBA significantly reduced PA-induced mRNA expressions of activating transcription factor 4 (ATF4), C/EBP homologous protein (CHOP), nuclear factor (erythroid-derived 2)-like 2 (NRF2), and intracellular ROS levels. Furthermore, NAC dramatically reduced PA-induced ROS levels and the mRNA expressions of NRF2, ATF4, and CHOP. L-citrulline pretreatment effectively rescued cell viability decreased by PA. Moreover, L-citrulline pretreatment significantly downregulated the PA-induced upregulation of GRP78, ATF4, and CHOP mRNA expression, and protein expression of p-PERK and cleaved caspase-3. PA increased intracellular ROS levels and NRF2 mRNA expression, whereas L-citrulline pretreatment remarkably reduced these levels. Conclusion Both ER and oxidative stresses interact during PA-induced cell death in MAC-T cells, and L-citrulline could attenuate this cell death by inhibiting ER and oxidative stresses. Therefore, L-citrulline may be a promising supplement for protecting against PA-induced cell death in bovine MECs during the lactation period of dairy cows.